Effect of Isocyanate Index on Physical Properties of Flexible Polyurethane Foams - C.S, Lee; T.L, Ooi; C.H, Chuah; S, Ahmad (Malaysian Journal of Science, 2007)
Water blown flexible polyurethane foams were made based on ratio 1:1 (w/w) mixture of palm oil-based polyester polyol with number average molecular weight (Mn) of 5000 and commercial polyether polyol with molecular weight of 5000,2.14 pph water and varying amounts of toluene diisocyanate (TDI). The effect of isocyanate index on the physical properties of flexible polyurethane was investigated. Isocyanate index of 100 produced the highest density foam (60.6 Kg/m3) with the lowest hysteresis (23.8%), good tensile strength (0.0995 MPa) and tear resistance (0.2468 N/mm).